Analysis on smooth handoff in NEMO route optimization protocols - Ahmed, Haram; Hassan Abdalla Hashim, Aisha; El-Azhary, Ismail; Islam, Shayla (IJCSNS, 2014)
With existing Network Mobility Basic Support (NEMO BS) protocol, entire transmissions are completely handled via Mobile Router (MR) to its home network on behalf of all Mobile Network nodes (MNNs) during movement among different networks. This concerns in enlarged length of route with higher delay and loss in best cases. Hence, in order to overcome these constraints, applying Smooth Handoff (SH) technique in Route Optimization (RO) for NEMO is an optimal solution. Consequently, the main aim of this paper is to offer a constructive analysis by doing analysis on some of the current approaches on soft handoff for RO in NEMO as well as discuss their strengths and weaknesses concerning delay and packet loss with some open issues.